Anthropometry and performance in wheelchair basketball - Granados, C.; Yanci, J.; Badiola, A.; Iturricastillo, A.; Otero, M.; Olasagasti, J.; Bidaurrazaga-Letona, I.; Gil, S. M. (The Journal of Strength and Conditioning Research, 2015)
This study investigated whether anthropometric characteristics, generic and specific sprinting, agility, strength, and endurance capacity could differentiate between First-Division and Third-Division wheelchair basketball (WB) players. A First-Division WB team (n = 8; age = 36.05 ± 8.25 years, sitting body height = 91.38 ± 4.24 cm, body mass = 79.80 ± 12.63 kg) and a Third-Division WB team (n = 11; age = 31.10 ± 6.37 years, sitting body height = 85.56 ± 6.48 cm, body mass = 71.18 ± 17.63 kg) participated in the study. Wheelchair sprint, agility, strength, and endurance tests were performed. The First-Division team was faster (8.7%) in 20 m without the ball, more agile (13-22%), stronger (18-33%), covered more distance (20%) in the endurance test, and presented higher values of rate of perceived exertion for the exercise load (48%) than the Third-Division team. Moreover, the individual 20-m sprint time values correlated inversely with the individual strength/power values (from r = -0.54 to -0.77, p = 0.05, n = 19). Wheelchair basketball coaches should structure strength and conditioning training to improve sprint and agility and evaluate players accordingly, so that they can receive appropriate training stimuli to match the physiological demands of their competitive level.